Improving Patient-centered Care: How Clinical Staff Overcome Barriers to Patient Engagement at the VHA. Issue 12 (December 2018) - Agha, Aneeza Z.; Werner, Rachel M.; Keddem, Shimrit; Huseman, Tiffany L.; Long, Judith A.; Shea, Judy A.
Abstract : Background: While patient engagement can be beneficial for patient care, there are barriers to engaging patients. These barriers exist for health care organizations, for health care personnel, and for the patients themselves. Solutions to barriers are not well documented. Objectives: Our objective was to explore barriers to patient engagement efforts and their corresponding solutions. Research Design: Qualitative interviews and site visits from a national sample of primary care facilities within the Veterans Health Administration were analyzed to understand patient engagement barriers and solutions. Sampling: We conducted a total of 155 phone and in-person semistructured interviews with primary care providers, mental health staff, social workers, pharmacists, patient advocates, health behavior coaches, and administrative staff at 27 Veterans Health Administration sites. Participants were asked to describe the obstacles they had to overcome in their efforts to improve patient engagement at their site. Results: Barriers to patient engagement are overcome by strategically updating data analytics; enhancing organization-wide processes and procedures; being creative with space design, staff hiring, and time commitments; cultivating staff collaborations; and addressing patient care issues such as access, customer service, and patient education. A key component of successful implementation is to create a culture, supported by leadership that promotes patient engagement. Conclusions: Participants understood the patient centered approach, despite experiencing a lack of resources and training and could push through solutions to patient engagement barriers while working within the limits of their settings. Abstract : Supplemental Digital Content is available in the text.